REACTIVE ARTHRITIS (SYN: REITER’S SYNDROME) - Antunes, João (2011)
Reactive arthritis, previously known as Reiter’s Syndrome, is the classic triad of arthritis, urethritis and conjunctivitis, which occurs after an acute episode of genito-urinary or gastrointestinal infection. In adults, the most frequent cause is infection by Chlamydia trahomatis. It may also present as an incomplete triad or be associated with dermatological or visceral symptoms. It is classified as a seronegative spondyloarthropathy, and is strongly associated with HLA-B27. Reactive arthritis may occur as an acute disease or progress to a chronic form, and treatment depends on the eliciting infection.